MdbHLH130, an Apple bHLH Transcription Factor, Confers Water Stress Resistance by Regulating Stomatal Closure and ROS Homeostasis in Transgenic Tobacco - Zhao, Qiang; Fan, Zihao; Qiu, Lina; Che, Qinqin; Wang, Ting; Li, Yuanyuan; Wang, Yongzhang (Frontiers in Plant Science, 2020)
Drought is a major environmental factor that significantly limits crop yield and quality worldwide. Basic helix-loop-helix (bHLH) transcription factors have been reported to participate in the regulation of various abiotic stresses. In this study, a bHLH transcription factor in apple, MdbHLH130, which contains a highly conserved bHLH domain, was isolated and characterized. qRT-PCR and PMdbHLH130::GUS analyses showed that MdbHLH130 was notably induced in response to dehydration stress. Compared with the wild-type (WT), transgenic apple calli overexpressing MdbHLH130 displayed greater resistance to PEG6000 treatment. In contrast, the MdbHLH130-Anti lines were more sensitive to PEG6000 treatment than WT. Moreover, ectopic expression of MdbHLH130 in tobacco improved tolerance to water deficit stress, and plants exhibited higher germination rates and survival rates, longer roots, and lower ABA-induced stomatal closure and leaf water loss than the WT control. Furthermore, overexpression of MdbHLH130 in tobacco also led to lower electrolyte leakage, malondialdehyde contents, and reactive oxygen species (ROS) accumulation and upregulation of the expression of some ROS-scavenging and stress-responsive genes under water deficit stress. In addition, MdbHLH130 transgenic tobacco plants exhibited improved tolerance to oxidative stress compared with WT. In conclusion, these results indicate that MdbHLH130 acts as a positive regulator of water stress responses through modulating stomatal closure and ROS-scavenging in tobacco.